1997
DOI: 10.1016/s0014-5793(97)00138-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing and expression of VAT, a CDC48/p97 ATPase homologue from the archaeon Thermoplasma acidophilum

Abstract: A member of the AAA family of Mg + -ATPases from the archaeon Thermoplasma acidophilum has been cloned and expressed in Escherichia coli. The protein, VCP-like ATPase of Thermoplasma acidophilum (VAT), is a homologue of SAV from Sulfolobus acidocaldarius and CdcH of Halobacterium salinarium, and belongs to the CDC48/VCP/p97 subfamily. The deduced product of the vat gene is 745 residues long (M r 83 000), which has an optimal Mg 2+ -ATPase activity at 70°C. Electron microscopy shows the purified protein to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…12-subunit configuration of PAN suggested that it may associate as two stacked hexameric rings similar to other related ATPases including the mammalian NSF (26), Thermoplasma VAT (48), and Rhodococcus ARC complexes (76). Transmission electron micrographs of the recombinant PAN proteins revealed particles of 10 to 14 nm in diameter which were somewhat ring-like but not distinct hexameric or symmetrical complexes (Fig.…”
Section: Purification Of the Proteasome-activating Nucleotidase (Pan)mentioning
confidence: 80%
“…12-subunit configuration of PAN suggested that it may associate as two stacked hexameric rings similar to other related ATPases including the mammalian NSF (26), Thermoplasma VAT (48), and Rhodococcus ARC complexes (76). Transmission electron micrographs of the recombinant PAN proteins revealed particles of 10 to 14 nm in diameter which were somewhat ring-like but not distinct hexameric or symmetrical complexes (Fig.…”
Section: Purification Of the Proteasome-activating Nucleotidase (Pan)mentioning
confidence: 80%
“…For the remaining proteases, some ORFs exhibit nonrandom distribution among representative strains. Of interest, vat.2, encoding hemoglobin protease (55), is present in all strains in group 1 but absent from group 2 strains (Table 5). Similarly, yeaZ, encoding a putative glycoprotein endopeptidase, is absent only in group 2 strains EC10 and RS168 (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Although many molecular details of ERAD remain unknown, recent work has identified valosin-containing protein (VCP) as a crucial cytoplasmic component of the process (Ye et al, 2001;Bays et al, 2001;Braun et al, 2002;Rabinovich et al, 2002;Jarosch et al, 2002). VCP is a widely distributed AAA ATPase also known as p97 in mammals and amphibians (Peters et al, 1990), TER94 in insects (Pinter et al, 1998), cdc48 in yeast (Moir et al, 1982;Frohlich et al, 1991) and VAT in Archaea (Pamnani et al, 1997). VCP is a ring-shaped homohexamer of a 97 kDa protein that contains two copies of the conserved ATP-binding domain characteristic of AAA family members and an N-terminal polyubiquitin-binding domain (Peters et al, 1990;Dai and Li, 2001).…”
mentioning
confidence: 99%